2004
DOI: 10.1063/1.1790731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macromolecular polymer structures on drag reduction in a turbulent channel flow

Abstract: This paper presents the influence of injected polymer solutions on turbulence in fully developed channel flows. In particular, it investigates the impact of concentration and mixing of the polymer solution on drag reduction. It is observed, via flow visualization and birefringence measurements, that for large injection concentrations macromolecular polymer structures exist in the flow. They are found to be mostly located in the neighborhood of the channel centerline. Laser Doppler velocimetry was used to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 40 publications
3
32
1
Order By: Relevance
“…The facility used for this study is described in detail in [13]. The flow in the recirculating water channel is driven by a 0.076 m 3 /s centrifugal pump into a 5.99 cm wide by 59.94 cm high and 6.35 m long channel test section.…”
Section: Facilities Instrumentation and Experimental Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…The facility used for this study is described in detail in [13]. The flow in the recirculating water channel is driven by a 0.076 m 3 /s centrifugal pump into a 5.99 cm wide by 59.94 cm high and 6.35 m long channel test section.…”
Section: Facilities Instrumentation and Experimental Proceduresmentioning
confidence: 99%
“…The experimental work on fully developed turbulent channel flows with polymer injection of Shen et al [20] and Kim et al [13] showed that for the same overall polymer concentration at the test section, larger drag reduction is obtained when polymer structures are present in the flow compared to a corresponding homogeneous polymer distribution. Kim et al [13] showed that the large bulk of the polymer structures concentrated in the neighborhood of the channel's centerline, inspite of injecting the polymer in the near wall region.…”
mentioning
confidence: 98%
See 3 more Smart Citations